Luokassa luokassa? : miten vanhempien status-tekijät vaikuttavat lasten toissijaiseen sosialisaatioon ja luokittumiseen ensimmäisinä kouluvuosina? - Kumpulainen, Janne (2011)
Bourdieu presented his theory of class and class reproduction and I'm interested in founding out how does socialization process affect this dynamic process in an egalitarian western country. Does educational system determine the future of the children by renewing the class structure or does the equal opportunities to succeed academically invalidate the reproduction cycle. By using longitudinal Alkuportaat-data (N=2258) from years 2006-2008 a co-variate analysis and a hierarchical modelling were made. Mathematical problem-solving and fluency in mother tongue were used as indicators for successful secondary socialization. The class structure is presented by parents' socio-economic status, degree of vocational training and family structure. Co-variate analysis suggests that there isn't a definitive connection between parents status variables and children’s school achievement. Thus it seems that Finnish elementary school breaks the reproduction cycle according to the co-variate analysis. Intracorrelates in the school and classroom clusters suggests that children's school achievement is explained by within-factors or the properties of a single student. Hierarchical model for Alkuportaat-data suggests that school is more important socializing environment for children than home. Reflecting back to previous studies on this matter it seems that Finnish society and educational policy supports the social-democratic ideal of equal opportunities for every citizen by taking the social classes out off the equation.